Cybercrimes: types, financial intelligence, use of special knowledge - Budnyk, Liudmyla; Karapetian, Olha; Metelskyi, Ihor (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
It was determined that the investigation of cybercrimes remains a difficult task for investigative bodies, which is due to the specificity of this type of crime; the difficulties of summarizing the investigative and judicial materials under consideration; the lack of methodological recommendations regarding the organization of the investigation of criminal acts and the tactics of operational and investigative activities; insufficient qualifications of investigators to work with specific sources of evidenceThe necessity of using special knowledge in the investigation of cybercrimes is substantiated; the sequence of tasks of computer and technical research using special knowledge in the process of investigating cybercrimes is determined, namely: identification of databases of a specialized program; identification of programs for creating tax reporting and electronic document management systems; detection of information about payments made using network technologies. Involvement of an expert or specialist is the investigator’s right, not an obligation. When investigating cybercrimes in the economic sphere, the problem arises of systematizing methodical approaches to the study of economic information in automated management systems in the light of complex computer-technical and economic expertise. It was concluded that when examining physical evidence in criminal cases regarding the investigation of economic cybercrimes, the most effective result will be a complex examination with the joint participation of experts in the field of economics and computer technology, since complexity is the most effective form of application of special knowledge. The requirements for the formulation of questions for research by an expert are important. An algorithm of tasks to be investigated using special knowledge in the investigation of cybercrimes in the field of economy is given. A typical task facing an expert is to search for databases with which work was performed, as well as to identify users who had access to one or another database, methods of approaching this task are highlighted.